Analisis kandungan unsur natrium, kalium, agnesium, kalsium dalam serum penderita gondok engan metoda spektrometri serapan atom - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK Atomic absorption spectrometry was used to determine sodium, potasium, magnesium and mlsium elements in sera of goiter patients in the Sawangan Sub-district and control group in the Mungkid Sub-district. The mean concentration of Na, K, Mg and Ca were 1,925, 136, 11.66 and 80 ppm respectively in the goiter area